Providing effective and preferred care closer to home: a realist review of intermediate care. (16th February 2015) - Pearson, Mark; Hunt, Harriet; Cooper, Chris; Shepperd, Sasha; Pawson, Ray; Anderson, Rob
Abstract Intermediate care is one of the number of service delivery models intended to integrate care and provide enhanced health and social care services closer to home, especially to reduce reliance on acute care hospital beds. In order for health and social care practitioners, service managers and commissioners to make informed decisions, it is vital to understand how to implement the admission avoidance and early supported discharge components of intermediate care within the context of local care systems. This paper reports the findings of a theory‐driven (realist) review conducted in 2011–2012. A broad range of evidence contained in 193 sources was used to construct a conceptual framework for intermediate care. This framework forms the basis for exploring factors at service user, professional and organisational levels that should be considered when designing and delivering intermediate care services within a particular local context. Our synthesis found that involving service users and their carers in collaborative decision‐making about the objectives of care and the place of care is central to achieving the aims of intermediate care. This pivotal involvement of the service user relies on practitioners, service managers and commissioners being aware of the impact that organisational structures at the local level can have on enabling or inhibiting collaborative decision‐making and care co‐ordination. Through all interactions with service users and their care networks, health and social care professionals should establish the meaning which alternative care environments have for different service users. Doing so means decisions about the best place of care will be better informed and gives service users choice. This in turn is likely to support psychological and social stability, and the attainment of functional goals. At an organisational level, integrated working can facilitate the delivery of intermediate care, but there is not a straightforward relationship between integrated organisational processes and integrated professional practice.